Senior tourism: A scientometric review (1998–2017) - Pestana, M.H.; Wang, W. - C.; Parreira, A. (Tourism Review, 2020)
Purpose: The purpose of this paper is to make a bibliometric analysis to reflect senior tourism research from 1998 until 2017, identifying their intellectual structure, emerging trends and future research opportunities. Design/Method/Approach: A detailed search of 700 core articles and 7,221 citations collated from Web-of-Science and Scopus was implemented and analysed through CiteSpace. Findings: The results reveal a slow increasing growth of research, with six main areas of research. The most cited articles are mainly older. The USA has solid leadership in publications, followed by Australia and China. The network of journals and Institutions show a core peripheral structure where Tourism Management and the University of Queensland are ranked first. The identification of structural holes, critical articles, and the development of new emerging tendencies highlights the priorities in the senior tourism domain, pointing to new opportunities for research. Originality: The originality of this paper consists of temporal and dynamic analysis of the last two decades, utilizing CiteSpace for a co-citation and co-occurrence network analysis.